Análise das propriedades psicométricas do Inventário de Aliança Terapêutica no tratamento fisioterápico de pacientes com dor lombar - Araujo, Amanda Costa [UNESP] (2014)
Low back pain is an extremely prevalent condition, affecting most of the population at some point in life, however the treatment of low back pain to date have small effects at best moderate. One factor often overlooked in clinical trials that may be interfering with the size of the treatment effect is the therapeutic alliance. The therapeutic alliance can be defined as the relationship of empathy between therapist and patient, consisting of three dimensions: bonds, goals and tasks. Based on these domains the questionnaire Working Alliance Inventory (WAI) was developed as a way to evaluate objectively the therapist patient relationship. Thus the purpose was to conduct an observational study to investigate the ability of the WAI questionnaire therapist and patient version, to evaluate the therapeutic alliance in low back pain patients undergoing physiotherapy treatment. The patient sample consisted of 100 individuals, of whom 54% were female. The (standard deviation) participants' average age of 47.8 (± 15.4) years and mean BMI of 27.7 (± 5.4) kg / m 2. A sample of therapists was consisted of 18 therapists, 77% female with a mean age of 25.6 (± 4.3) years. Data were collected at three times: after the first session, before the second session and two months after the first session...